ASPECTS OF LINGUISTIC USAGE IN ELEGY WRITTEN IN A COUNTRY CHURCHYARD BY THOMAS GRAY - Quadri, Kahkasha Moin; Yadav, Meenakshi Sharma; Yadav, Manoj Kumar (International Journal of Research -GRANTHAALAYAH, 2022)
Poetic language includes three key components: sound, shape, and sense. However, every poem has its own context and is an intertext with other poems. Therefore, the substantial use of alliteration, rhyming, lyrical expression, and clichés, as well as other language devices that bring attention to words, sounds, or other device decorations, is a necessary tool and trick in the scientific production of poetry. This article explored to inspect the aspects of linguistic usage in the forms of semantics that are accomplished in the poetic and figurative language of Thomas Gray's Elegy Written in a Country Churchyard, which aimed to examine the influence of lexical knowledge in language and literature and how it enhances inventiveness. Even though this poem speaks of ordinary people, and an expression of sympathy and support for those who have the misfortune to be without money or social prestige in the literary sense. The involvement of syntactic-semantic factors, viz., presupposition and entailment, make the poem more vivid to the reader. Furthermore, the poem Elegy contains hyponyms and synonyms, accompanied by a semantic echo. This study focuses on lexical relations included in the poem through syntagmatic and paradigmatic word descriptions. Further, this study examines those ambiguous words that generate complexity between the speaker/writer and their listener/reader. It has been discovered that various aspects of semantics form a nexus between the theme and word formation in poetry.